The Impact of Task-Based Language Teaching on Students’ Listening Proficiency Using Song Lyrics - Mareta Putriani; Intan Hamzah (International Journal of Research in Education, 2026)
This research focuses on assessing the effectiveness of the Task-Based Language Teaching (TBLT) approach combined with English song lyrics in improving students' listening skills and analyzes the connection between students' perceptions and their listening outcomes. A quasi-experimental design was utilized with 59 tenth-grade students from a senior high school in Bandar Lampung,  divided into an experimental group (n = 30) and a control group (n = 29).The experimental group participated in five TBLT-focused lessons that included English song lyrics, whereas the control group underwent traditional listening instruction. Data were gathered via pre- and post-listening assessments and a 15-item Likert-scale survey. Findings indicated that the experimental group demonstrated a substantially higher enhancement in listening performance, recording an average post-test score of 92.50 (SD = 9.53) versus the control group's average of 53.96 (SD = 18.63). Responses to the questionnaire revealed very favorable views across three areas (mean range = 4.5–4.7), such as the learning environment, the use of songs as educational tools, and teaching effectiveness. Pearson's correlation analysis revealed a highly strong and significant positive association between perception scores and listening performance (r = 0.992, p < 0.001). Results indicate that incorporating song lyrics into TBLT produces a synergistic impact where emotional involvement and cognitive understanding support one another, making it a particularly effective teaching approach for EFL classrooms.